VPOD: virtual parking overlay network based data delivery in urban VANETs. (2017) - Zhu, Jinqi; Ma, Chunmei; Liu, Nianbo; Liu, Ming; Feng, Weijia
Vehicular ad hoc networks (VANETs) have characteristics of intermittent connectivity, high mobility of vehicle nodes and dynamic topology, which make data delivery in VANETs very challenging. Pervious works that based on history traffic patterns to predict the current traffic conditions on the roads are not accurate. Moreover, deploying roadside units (RSUs) is a possible solution to overcome the challenges, but it often requires a large amount of investment. Motivated by the fact that there are large amounts of outside parked vehicles in urban areas, we propose a virtual parking overlay network based data delivery scheme (VPOD), which does not need any RSUs but leverages a parking overlay network formed by outside parked vehicles to disseminate messages among moving vehicles. Simulation results based on a real city map and realistic traffic situations show that VPOD achieves high performance in data delivery, especially in sparse traffic and multiple requests conditions.